Revitalisasi Hukum Progresif Analisis Filsafat Atas Paradigma dan Dinamika Perubahan Hukum - Anita Audina; Siti Hawa Ainul; Marjan Marjan; Oki Sadewo Setyo; Elviandri Elviandri (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Post-reform law enforcement in Indonesia continues to face serious challenges in the form of stagnation due to the dominance of a rigid and procedural legal positivism paradigm (legal-formalistic). This condition often causes the law to fail in delivering substantive justice, turning humans merely into objects of legislation. This study aims to revitalize Satjipto Rahardjo's progressive legal theory through a comprehensive philosophy of science approach, encompassing ontology, epistemology, and axiology, to offer a solution to the deadlock in the national legal system. The research method employed is normative juridical with philosophical and conceptual approaches, analyzing primary legal materials from Satjipto Rahardjo's works and related secondary literature. The findings indicate that ontologically, progressive law rejects the status quo and views law as a fluid institution (law in the making) intended to serve human beings. Epistemologically, legal validity is derived not only from regulatory texts (law in the books) but also from social reality, spiritual intelligence, and the conscience of law enforcers (law in action). Axiologically, the orientation of law is shifted from formal certainty toward human happiness and welfare. The conclusion of this study confirms that integrating the progressive paradigm is essential to reforming the mentality of law enforcement officials, encouraging them to courageously undertake rule-breaking when facing formal deadlocks, for the sake of realizing a legal state based on conscience and social justice.